OPTIMALISASI PELAKSANAAN KKN STKIP MUHAMMADIYAH MUARA BUNGO PADA MASA PANDEMI COVID 19 DI KABUPATEN MERANGIN - Apdoludin Apdoludin; Titis Wulandari; Tri Wera Agrita; Nurlev Avana (LP3M STKIP MUHAMMADIYAH MUARA BUNGO, 2023)
The COVID-19 pandemic has changed various aspects of human life today, especially in the world of education. This pandemic era requires all elements of education to adapt in carrying out learning activities at the elementary, junior high, high school up to university levels. This study aims to review the strategy for implementing KKN for STKIP Muhammadiyah Muara Bungo students during the COVID-19 pandemic. Therefore, community service activities regarding optimization strategies for the implementation of KKN are considered important for field supervisors. The method used in the implementation of community service is the lecture and discussion method. Activities are carried out in the following stages: 1) preparation of the required documents, 2) implementation of activities, and 3) evaluation of the achievement of objectives. The results of this activity are as follows: 1) preparation of required documents, 2) implementation of activities, and 3) evaluation of goal achievement. The results of this activity are as follows: 1) the required documents are completed according to plan, 2) the activity is attended by all KKN DPLs, and 3) KKN DPLs are very enthusiastic in receiving an explanation of the concept of optimizing the implementation of KKN and 4) KKN DPL gain knowledge about strategies for optimizing the implementation of STKIP Muhammadiyah Muara Bungo KKN during the Covid 19 period.